Appropriate Musical Metaphors - Zangwill, Nick (The Nordic Journal of Aesthetics, 2009)
I argue that we should avoid a unitary account of what makes metaphorical descriptions of music in terms of emotion appropriate. There are many different ways in which musical metaphors can be appropriate. The right view of metaphorical appropriateness is a generously pluralist one.